2017
DOI: 10.1371/journal.pone.0181573
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the potato WRKY transcription factor family

Abstract: WRKY transcription factors play pivotal roles in regulation of stress responses. This study identified 79 WRKY genes in potato (Solanum tuberosum). Based on multiple sequence alignment and phylogenetic relationships, WRKY genes were classified into three major groups. The majority of WRKY genes belonged to Group II (52 StWRKYs), Group III had 14 and Group I consisted of 13. The phylogenetic tree further classified Group II into five sub-groups. All StWRKY genes except StWRKY79 were mapped on potato chromosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 61 publications
(107 reference statements)
5
56
1
Order By: Relevance
“…Despite this, to date no studies have examined WRKY gene family components and their different characteristics in wild potato species. A few data on this gene family are available only in the cultivated potato, where Zhang et al 21 , Liu et al 22 and Cheng et al 12 identified 79, 82 and 81 StWRKYs, respectively. Previously, Dellagi et al 23 identified StWRKY1 as a good candidate for functional studies, and Shahzad et al 24 overexpressed it in potato.…”
mentioning
confidence: 99%
“…Despite this, to date no studies have examined WRKY gene family components and their different characteristics in wild potato species. A few data on this gene family are available only in the cultivated potato, where Zhang et al 21 , Liu et al 22 and Cheng et al 12 identified 79, 82 and 81 StWRKYs, respectively. Previously, Dellagi et al 23 identified StWRKY1 as a good candidate for functional studies, and Shahzad et al 24 overexpressed it in potato.…”
mentioning
confidence: 99%
“…Correspondingly, it also had the shortest length of protein. Be different with other gene family, such as WRKY [28], the motifs in subgroup proteins had no significantly differences. Because the GH3 proteins combined amino acids to different acyl acid substrates, they must have had the corresponding active site.…”
Section: Structural Analysis Of Gh3 Proteinsmentioning
confidence: 66%
“…We defined paralogous genes as those existing in the same chromosome within a 50-kb physical distance that were tandem duplicated pairs [28,33]. The segmental duplication of each gene was ensured through Plant Genome Duplication Database (PGDD) website (http://chibba.agtec.uga.edu/duplication/).…”
Section: Analysis Of Gene Duplicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can obtain many genes that response to MYB transcription factor of F. tataricum under salt stress. As an important transcription factor superfamily, WRKY transporters are involved in response to environmental stimuli, such as high salt, low temperature, etc [52]. This transcription factor family in F. tataricum is highly up-regulate under salt stress, which has the complexity and importance of stress regulation.…”
Section: Discussionmentioning
confidence: 99%